The introduction of new hosts with human trade shapes the extant distribution of Toxoplasma gondii lineages - (:unkn) unknown (My University, 2019)
Abstract: Toxoplasma gondii is a zoonotic protozoan with a worldwide occurrence, but the determinants of the current pattern in the geographical distribution of T. gondii lineages and strains remain poorly understood. To test the influence of human trade on T. gondii populations, we conducted a population genetic study of 72 T. gondii animal isolates from Senegal, a West African country in which the ongoing inland progress of invasive murine hosts (introduced in port cities of Senegal since the 16th century by European sailors) is well described. Isolates were mainly collected on free-range poultry, which are considered as relevant bioindicators of T. gondii strain diversity in the domestic environment. Sampling was conducted in two port cities of Senegal (Dakar and Saint-Louis) and in one inland region (Kedougou). Population genetic analyses using 15 microsatellite markers revealed different patterns between port cities where lineages non-virulent for mice (type II, type III, and Africa 4) were predominant, and Kedougou where the mouse-virulent Africa 1 lineage was the most common. By considering the current spatial pattern in the inland progress of invasive rodents in Senegal, our results suggest that the invasive house mouse Mus musculus domesticus counter-selects the Africa 1 lineage in the invaded areas. The comparison of the microsatellite alleles of type II strains from Senegal to type II strains from other areas in Africa and Western Europe, using discriminant analysis of principal components and Network analysis, point to a mainly Western European origin of the type II lineage in Senegal. Collectively, these findings suggest that human-mediated intercontinental migrations of murine hosts are important vectors of T. gondii strains. Differential susceptibility of endemic and introduced murine hosts to various T. gondii strains probably determines the persistence of these strains in the environment, and therefore their availability for human and
Keywords: African Research